ANALYSIS OF PHYSICAL AND CHEMICAL PARAMETERS OF WATER QUALITY AS AN INDICATOR OF WATER POLLUTION IN THE LAENDE RIVER, MUNA REGENCY - Ian, Ian Adi Gunawan; Tosepu , Ramadhan; Kete, Surya Cipta Ramadhan (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2025)
Water is essential for life and is used for various daily needs. Rivers as one of the main water sources are often used by the community but are also used as waste disposal sites. The Laende River in Muna Regency has experienced a decline in water quality due to community activities, domestic and agricultural waste, and environmental damage in the river basin. This study aims to analyze the water quality of the Laende River based on physical and chemical parameters as indicators of pollution. The method used is descriptive quantitative through field surveys and laboratory analysis. Water samples were taken from three river segments: upstream, middle, and downstream. The parameters analyzed include temperature, TDS, TSS, pH, BOD, COD, DO, Fe, nitrate, and sulfate. The test results were compared with the class I river water quality standards according to PP No. 22 of 2021. The results show that the water quality of the Laende River decreases from upstream to downstream. The parameters of TSS in the upstream segment (44 mg/L), BOD (2.60–3.10 mg/L), COD (10.22–14.20 mg/L) and DO (4.48–5.31 mg/L) exceeded the established quality standards. This condition indicates significant organic pollution and anthropogenic activities along the river. This finding emphasizes the need for sustainable water quality management and control of pollution sources in the Laende River Watershed.